Libyan Foreign Policy amid Contemporary Geopolitical Transformations: Challenges to the Reconstruction of Libya’s Regional and International Role - Ahmed Meftah Fallag; Khiria Mohamed Alddaghil (Journal of Scientific and Human Dimensions, 2026)
This study aims to analyze Libyan foreign policy in light of current geopolitical shifts and to demonstrate the extent to which these shifts impact efforts to rebuild Libya’s regional and international role. The study is based on the premise that Libya’s ability to regain its regional and international standing is largely dependent on its success in achieving internal political and institutional stability and its capacity to engage positively with the geopolitical changes occurring in the regional and international environment. The study employs a descriptive-analytical approach, drawing on role theory as a theoretical framework for explaining state behavior. It examines the internal and external determinants of Libyan foreign policy and discusses the most prominent geopolitical shifts in the Mediterranean, North Africa, and the Sahel-Saharan region and their implications for Libyan foreign policy orientations. The findings also reveal that Libya’s unique geopolitical location and its natural and strategic resources present a significant opportunity to enhance its regional and international standing if these are utilized within a clear strategic vision and effective state institutions. The study concluded that rebuilding Libya’s regional and international role requires adopting a more effective and flexible foreign policy based on strengthening internal stability, developing institutional and diplomatic performance, and leveraging current geopolitical shifts to serve Libyan national interests and enhance its presence in its regional and international environment.